AN EFFICIENT MICROWAVE ASSISTED MULTICOMPONENT SYNTHESIS OF SOME 7-AMINO-3-(SUBSTITUTED PHENYL)-5-(SUBSTITUTED PHENYL)-[1,2,4]TRIAZOLO[4,3A]PYRIMIDINE-6-CARBONITRILE DERIVATIVES - DIVATE, VITTHAL A.; DHONGADE-DESAI, SAVITA (International Journal of Current Pharmaceutical Research, 2014)
A series of 7-amino-3-(substituted phenyl)-5-(substituted phenyl)-[1,2,4]triazolo [4,3a] pyrimidine-6-carbonitrile derivatives were synthesized from 4-amino-2-hydroxy (OR mercapto)-6-(substituted phenyl)-pyrimidine-5-carbonitrile, hydrazine hydrate and aromatic aldehydes. The derivatives were obtained in good yields by the microwave-assisted one-pot protocol in very short reaction time. The synthesized compounds were studied for QSAR by subjecting to a prediction of biological activities applying computer programme PASS. It is found that 7-Amino-3-(4-chloro-phenyl)-5-(2,4-dichloro-phenyl)-[1,2,4]triazolo[4,3-a]pyrimidine-6-carbonitrile is a promising anticonvulsant agent; which can be synthesized by an efficient, promising, and green synthetic method with high yield.